Pendidikan Karakter Islami Dalam Tradisi Nyabis Masyarakat Madura - Maulidi, Achmad; Wardi, Moh.; Mubarok, Ghozi; Ahmad, Ahmad (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2022)
As a religious and fanatical ethnicity, Madura's people has practiced the values of the Madura’s character which has been and has become an identity for a long time, an attitude of resignation, courtesy, and empathy. The distinctive Maduran character does not escape the influence of a kiai as the main character in the nyabis tradition who historically and in reality is an expert in religious science and is very influential for the Madurese community. The purpose of this study is to find out the values of Islamic character in the nyabis tradition and how people internalize these values in everyday life. This research is a qualitative research type of phenomenological study, the methods for collecting data are interviews (semi structured), participant and non-participant observation, and documentation. To process data: data reduction, data presentation, data verification. The research findings show that the values of Islamic character in the nyabis tradition are the values of aqidah, ubudiah and ahlakul karimah values. These three values then become a norm that is commonly used as a basis in everyday life.